SELECTION INDICES FOR YIELD IMPROVEMENT IN WHEAT (TRITICUM AESTIVUM L.) IN NORMAL IRRIGATION CONDITION UNDER LATE SOWN CONDITION - V. R. ATRAM; D. M. PANCHABHAI; SHANTI PATIL; SHALINI BADGE (The Bioscan, 2015)
Fortytwo hybrid tea rose varieties were used to identify suitable parents for hybridization programme.Pollen morphology were rough in 14, smooth in 9 and medium smooth in 19 varieties. Stigmas wereeither Capitate or Flat capitates in shape. Pollen diameter and pollen viability ranged from 5.26μm to 3.80μm and from 70.13% to 38.86% respectively. Range for in vitro pollen germination was from 72.62% to 40.26% . Stigma size ranged from 41.88 μm to 21.56 μm and only 20 varieties set hips.Based on laboratory studies Melame, Montreal, Bonnie Nuit, Kentucky Derby, Chardony, Kiss of Fire and National Trust as pollen parents and Milky Way, Angel Delight, Forever, Duet, Chablis, Alliance, Grand Masterpiece, Miss Liberte, Apricot Spice, Royal Show, and Queen Elizabeth as female parentswere identified. Actual crossing programmewhen carried out, only 31 crosses produced more than 20 seeds which involved six females and all seven males identified.Hence, it is concluded that Melame, Montreal, Bonnie Nuit, KentuckyDerby, NationalTrust, Chardony and Kiss of Fire as male parent and MilkyWay, Forever, Alliance, Grand Masterpiece, RoyalShow and Queen Elizabethas female parents were identified to be used as parents to enhance the genetic variability in hybridization between hybrid tea roses.